Bosutinib: a SRC–ABL tyrosine kinase inhibitor for treatment of chronic myeloid leukemia - El Rassi F; Khoury HJ (Dove Medical Press, 2013)
Fuad El Rassi, Hanna Jean KhouryDivision of Hematology, Department of Hematology and Medical Oncology, the Winship Cancer Institute at Emory University, Atlanta, Georgia, USAAbstract: Bosutinib is one of five tyrosine kinase inhibitors commercially available in the United States for the treatment of chronic myeloid leukemia. This review of bosutinib summarizes the mode of action, pharmacokinetics, efficacy and safety data, as well as the patient-focused perspective through quality-of-life data. Bosutinib has shown considerable and sustained efficacy in chronic myeloid leukemia, especially in the chronic phase, with resistance or intolerance to prior tyrosine kinase inhibitors. Bosutinib has distinct but manageable adverse events. In the absence of T315I and V299L mutations, there are no absolute contraindications for the use of bosutinib in this patient population.Keywords: bosutinib, chronic myeloid leukemia, treatment, review, SRC-ABL kinase inhibitor, clinical activity